Pengaruh Transformasi Digital dan Karakteristik Perusahaan terhadap Audit Report Lag (Studi Empiris pada Perusahaan Sektor Properti & Real Estate yang Terdaftar di BEI pada Periode 2020-2023) - Fitrianda, Linta Desti; Rosadi, Samsul (Jurnal EMT KITA, 2026)
This study examines the influence of digital transformation and company characteristics on audit report lag in property and real estate firms listed on the Indonesia Stock Exchange from 2020 to 2023. Using a quantitative approach with panel data, the study analyzes 75 companies with a total of 282 observations selected through purposive sampling method, ensuring that the sample meets the required research criteria and provides consistent reporting throughout the analysis period. Panel regression with the Random Effect Model shows that digital transformation and profitability significantly reduce audit report lag, indicating that higher digital adoption and stronger financial performance support more efficient audit processes. Meanwhile, intangible assets, firm size, leverage, and auditor reputation (Big4) do not significantly affect audit report lag. These findings highlight that internal company capabilities, particularly digital readiness and profitability, play a more critical role in ensuring timely audit completion compared to structural firm characteristics.